Pengujian Kesuksesan Implementasi Sistem Informasi Akuntansi Lembaga Keuangan Mikro: Modified Delone Mcleon Model - Wahyu Manuhara Putra; Muh. Alfian (Journal of Accounting and Investment, 2016)
This research is motivated by the importance of accounting software in the micro finance institutions led by UPK that has an important role as a catalyst for poverty alleviation. Various data dan field observations indicate that the financial system various LKM UPK has not shown the quality reliable dan relevant system performance, even accounting stdanards has not fully implemented. This study adapted the DeLone dan McLean model that has been modified McGill et al. (2003) to map dan design the essential components of a successful implementation of accounting software for individual users as well as analyzing various system variables on user satisfaction, dan the impact on individual performance. All hypotheses have been tested dan found to result impartial. This model will be the basis for making a prototype web-based accounting softaware that will be developed dan implemented in the second year. So the ultimate goal of this research is that microfinance institutions are able to be an instrument of poverty alleviation optimal sustainability.